A needs analysis for a non-abusive intervention programme in the School of Health Care Sciences at the University of Pretoria - LO Fouché; R du Toit (AOSIS, 2006)
Due to feedback from students, student abuse during fieldwork, was brought to the attention of the researchers. The study aimed to determine whether a need for a nonabusive intervention programme (NIP) existed amongst the School of Health Care Science students at the University of Pretoria. All students enrolled at the School of Health Care Sciences completed a questionnaire. An overwhelming response indicated that the majority of students (95.85%) have a need for a non-abusive intervention programme (NIP). A significant need was identified especially among Nursing-, Physiotherapy- and Radiography students, 2nd and 4,h year students, and within a psychiatric fieldwork setting. Two surprise findings were firstly, that students who have no history of abuse have a greater need for an intervention programme than students with a history of abuse. Secondly superiors in the field are responsible for the majority of abusive incidences reported by students. The implementation of a non-abusive intervention programme (NIP) to help students handle abusive incidences effectively and humanely is strongly recommended.